The Impact of Social Media, Tour Packages, and Word-of-Mouth on Visit Intention to Jaco Island, Timor-Leste. - Grilo dos Santos, Colly; Wisnawa, I Made Bayu; Subadra, I Nengah (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Tourism is one of the largest industries in the world and serves as a cornerstone for the economic development of various countries. Timor Leste, as a nation with significant tourism potential, relies on this sector to support its economic growth. With its diversity of culture, traditions, and natural beauty, tourism in Timor Leste plays a crucial role as a source of national income, ranking third after oil and agriculture. This research aims to examine the influence of social media, tour packages, and word of mouth (WOM) on the interest in visiting Jaco Island in Timor Leste. The method used in this study is a survey approach with a quantitative framework. Data were collected through questionnaires to identify the influence of independent variables, namely Social Media, Tour Packages, and Word of Mouth (WOM), on the dependent variable, which is the interest in visiting. The results indicate that social media, tour packages, and WOM significantly affect the interest in visiting Jaco Island. Together, these three variables contribute significantly to shaping the interest in visiting. The WOM variable is the most influential on the interest in visiting, evidenced by a path coefficient of 0.527, indicating that each unit increase in WOM will increase the interest in visiting by 52.7%. Social media, tour packages, and Word of Mouth (WOM) have a significant impact on the interest in visiting Jaco Island. Among these three variables, WOM is the most influential, with a 52.7% increase in the interest in visiting for every unit increase in WOM.